Empowering Personal Financial Management Through Islamic Spirituality and Financial Independence (Freedom) - Sambharakreshna, Yudhanta; Wulandari, Anis (Journal of International Conference Proceedings, 2024)
The significance of this research lies in combining Islamic spiritual values with financial strategies aimed at achieving financial well-being, as well as emotional and spiritual balance. The primary objective of this study is to explore the Islamic spirituality role and financial freedom in individuals’ financial management. This study employs a quantitative approach using a survey method. The population comprises Muslim entrepreneurs, and the sample was selected through purposive and convenience sampling techniques. Data were analyzed using multiple linear regression to examine the effect of Islamic spirituality and financial freedom towards to personal financial management. The findings reveal that Islamic spirituality significantly impacts personal financial management. Additionally, financial freedom has a positive effect on the quality of financial management. The results further indicate that integrating Islamic spirituality with financial freedom can enhance individuals’ financial management abilities. This study contributes not only to achieving effective financial management but also to improving psychological and social well-being. The implications of these findings suggest that financial management strategies grounded in Islamic spirituality can be integrated with financial freedom to strengthen individual financial stability while also reducing social pressures.